Case Report: Are We Witnessing an Increase of Chronic Ascending Aortic Dissection as a Collateral Effect to the COVID-19 Pandemic? - Lyon, Arnaud; Gunga, Ziyad; Niclauss, Lars; Rancati, Valentina; Tozzi, Piergiorgio (Frontiers in Cardiovascular Medicine, 2021)
Background: The COVID-19 pandemic is reducing healthcare accessibility to non-life threating diseases, thus hiding their real incidence. Moreover, the incidence of potentially fatal conditions such as acute type A aortic dissection seems to have decreased since the pandemic began, while the number of cases of chronic ascending aortic dissections dramatically increased. We present two patients whose management has been affected by the exceptional sanitary situation we are dealing with. Case report: A 70-year-old male with chest pain and an aortic regurgitation murmur had his cardiac workup delayed (4 months) because of sanitary restrictions. He was then diagnosed with chronic type A aortic dissection and underwent urgent replacement of ascending aorta and aortic root. The delay in surgical treatment made the intervention technically challenging because the ascending aorta grew up to 80mm inducing strong adhesions and chronic inflammation. The second case report concerns a 68-year-old female with right lower-limb pain who was diagnosed with deep-vein thrombosis. However, a CT Scan to exclude a pulmonary embolism could not be realized until five months later because of sanitary restrictions. When she eventually got the CT scan, it fortuitously showed a chronic dissection of the ascending aorta. She underwent urgent surgery and the intervention was challenging due to adhesions and severe inflammation. Conclusion: Delayed treatment due to sanitary restrictions related to COVID-19 pandemic is having a significant impact on the management of potentially life-threatening conditions including type A aortic dissection. We should remain careful to avoid COVID-19 also hitting patients who are not infected with the virus.